2022
DOI: 10.3389/fpubh.2021.755166
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Healthcare Project Implementation in a Hierarchical Tertiary Hospital: Lessons Learned

Abstract: An important innovation in healthcare is the value-based healthcare (VBHC) framework, a way to solve health services' sustainability problems and ensure continuous improvement of healthcare quality. The Quality and Safety Unit at the Hospital Universitario 12 de Octubre has been since May 2018 coordinating the implementation of several healthcare innovation projects within the paradigm of VBHC. Implementing innovations in a complex institution, such as a tertiary hospital, is a challenge; we present here the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Another study mentioned that a set of Key Performance Indicators (KPI) for healthcare professionals need to be created to provide knowledge about all of the achievements/failures in health care. This way, the awareness of the importance of IPU can increase among the healthcare professionals (Annabathula et al, 2021;Cossio-Gil et al, 2022;Goretti et al, 2020;Heijsters et al, 2022;Nilsson et al, 2017;Nojszewska & Sielska, 2022;Varela-Rodríguez et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study mentioned that a set of Key Performance Indicators (KPI) for healthcare professionals need to be created to provide knowledge about all of the achievements/failures in health care. This way, the awareness of the importance of IPU can increase among the healthcare professionals (Annabathula et al, 2021;Cossio-Gil et al, 2022;Goretti et al, 2020;Heijsters et al, 2022;Nilsson et al, 2017;Nojszewska & Sielska, 2022;Varela-Rodríguez et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is clearly essential to know how patients define value, otherwise the risk exists that care development will focus on what is easy to measure instead of what is most important and of greatest value to the patients. Some major factors affecting the implementation of measuring outcome and cost are (i) data infrastructure, (ii) a systematic approach for the identification of improvement potential and the selection and implementation of improvement initiatives, (iii) governance in which roles and responsibilities of physicians regarding outcome improvement are formalized, and (iv) implementation of outcomes within hospital strategy, policy documents, and the planning and control cycle (Ahmed et al, 2019;Allen et al, 2021;Amini et al, 2021;Bodar et al, 2020;Colldén & Hellström, 2018;Cossio-Gil et al, 2022;Goretti et al, 2020;Kuklinski et al, 2020;Lansdaal et al, 2022;Marotta et al, 2020;Nilsson et al, 2017;Ramos et al, 2021;Rutherford et al, 2021;Schraut et al, 2022;St John et al, 2021;Van Veghel et al, 2020;Varela-Rodríguez et al, 2021;Zipfel et al, 2019). In moving to bundled payments, many current initiatives have been successfully centered on creating bundled payments for surgical care to reduce cost.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Verela-Rodríguez et al [49] described VBHC as 'an international trend that implies significant changes at several levels of the healthcare institutions from managerial viewpoints to the doctor-patient relationship'.…”
Section: Definitions Of Value-based Carementioning
confidence: 99%
“…A total of nine studies considered the presence of leadership as a key element to support and guide the (multidisciplinary) teams implementing the VBHC approach within the hospital: Nilsson et al [41,43]; Hejister et al [45]; Daniels et al [44]; Cossio et al [32]; NG [47]; Steinman et al [48] and Varela et al [49]. According to Nilsson et al [41,43], effective leadership occupies a role within the team that is persevering, committed throughout the process, able to motivate and drive the team, and is constantly able to bring new ideas and approaches.…”
Section: Key Elements Of Implementing and Delivering Value-based Carementioning
confidence: 99%
“… New Health Information System structure implies the inclusion of data from primary sources (professional, patient, administrative databases and medical devices, including wearables) in centralized data warehousing and the development of means to extract the different information outputs from a unique data entry, answering to individual healthcare needs as much as the information requirements for administrative, public health and research purposes [QoL, Quality of Life; RWE, Real World Evidence; CROM, clinician-reported outcome measures (clinical indicators); PROM, patient-reported outcome measures (quality of life health outcome indicators); PREM, patient-reported outcome measures (patient experience indicators); MDRM, Medical Devices-Reported Measures (clinical indicator measured by medical devices); ADB, Administrative Databases (patient information from administrative databases include social determinants of health)]. Source: Modified with author's permission from Varela-Rodríguez et al ( 5 ). …”
mentioning
confidence: 99%